2021
DOI: 10.1111/nin.12411
|View full text |Cite
|
Sign up to set email alerts
|

“He just teaches whatever he thinks is important”: Analysis of comments in student evaluations of teaching

Abstract: Student evaluations of teaching are ubiquitous in higher education, widely disliked by faculty, and of uncertain value. The research literature on both their technical validity and their pragmatic utility is unusually polarized, with adamant opponents and defenders.Student evaluations generally consist of two parts: first, a series of questions with Likert-scale type answers (hereafter referred to as the numeric ratings), and second, an unstructured space for comments. Almost all of the existing research has f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
(79 reference statements)
1
5
0
Order By: Relevance
“…First, this study confirms the limited SET impact even in a context where teaching is highly valued. It aligns with various studies in global higher education, showing an emphasis on SET ratings without collaborative problem solving combined with qualitative inquiry, pedagogical reflection and professional support would bring minimal impact on improvement (Padgett, 2021; Thompson, 2013). The administrators commonly perceived roles as middle managers rather than professional developers, leading to their predominant monitoring and disengaging approaches to SET.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…First, this study confirms the limited SET impact even in a context where teaching is highly valued. It aligns with various studies in global higher education, showing an emphasis on SET ratings without collaborative problem solving combined with qualitative inquiry, pedagogical reflection and professional support would bring minimal impact on improvement (Padgett, 2021; Thompson, 2013). The administrators commonly perceived roles as middle managers rather than professional developers, leading to their predominant monitoring and disengaging approaches to SET.…”
Section: Discussionsupporting
confidence: 77%
“…First, multiple global studies have revealed an overreliance on using SET for judgmental and accountability purposes has diminished the professional values of teaching, learning and community engagement in higher education (Mutch and Tatebe, 2017; Padgett, 2021). In New Zealand, SET has been primarily used for institutional compliance with audit-governing bodies (Norsworthy and Sanders, 2021), shifting its original purpose of supporting teaching and learning to a more bureaucratic practice (Barrow and Grant, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Forgive me. However, while a great deal of attention focuses on student evaluations of teaching (Padgett, 2021), educational skills development (see e.g. Cayir & Ulupinar, in press), and the complexity of health education (Pueyo‐Garrigues et al, 2021), epistemic competence of the sort discussed in this paper is inadequately addressed by nurse educators—and here I include myself.…”
Section: Prescriptionmentioning
confidence: 99%
“…Forgive me. However, while a great deal of attention focuses on student evaluations of teaching (Padgett, 2021), educational skills development (see e. In conclusion, this is not an attack upon nurse education, professionalism or professionalization. Quite the reverse.…”
Section: Pre Scrip Tionmentioning
confidence: 99%